2017
DOI: 10.1007/s00134-017-4920-z
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for mechanical ventilation of critically ill children from the Paediatric Mechanical Ventilation Consensus Conference (PEMVECC)

Abstract: PurposeMuch of the common practice in paediatric mechanical ventilation is based on personal experiences and what paediatric critical care practitioners have adopted from adult and neonatal experience. This presents a barrier to planning and interpretation of clinical trials on the use of specific and targeted interventions. We aim to establish a European consensus guideline on mechanical ventilation of critically children.MethodsThe European Society for Paediatric and Neonatal Intensive Care initiated a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
203
0
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(229 citation statements)
references
References 211 publications
3
203
0
23
Order By: Relevance
“…However, noninvasive ventilation should be reserved for children with sepsis who are responding to initial resuscitation, do not have evidence for ongoing or worsening end-organ dysfunction, and in whom close monitoring and frequent reevaluation can be ensured [253,255,259]. This recommendation for children with sepsis-induced PARDS aligns with the 2015 PALICC [260] and 2017 Pediatric Mechanical Ventilation Consensus Conference (PEMVECC) [261] guidelines.…”
Section: We Suggest a Trial Of Noninvasive Mechanical Ventilation (Ovmentioning
confidence: 99%
See 3 more Smart Citations
“…However, noninvasive ventilation should be reserved for children with sepsis who are responding to initial resuscitation, do not have evidence for ongoing or worsening end-organ dysfunction, and in whom close monitoring and frequent reevaluation can be ensured [253,255,259]. This recommendation for children with sepsis-induced PARDS aligns with the 2015 PALICC [260] and 2017 Pediatric Mechanical Ventilation Consensus Conference (PEMVECC) [261] guidelines.…”
Section: We Suggest a Trial Of Noninvasive Mechanical Ventilation (Ovmentioning
confidence: 99%
“…In 2017, a multicenter observational study by the Collaborative Pediatric Critical Care Research Network reported that pediatric critical care clinicians almost uniformly limit PEEP to 10 cm H2O irrespective of oxygenation and Fio2 [264]. This is in contrast to the PEMVECC [261] and PALICC [24] recommendations for use of PEEP in excess of 15 cm H2O for severe PARDS patients. Our panel reviewed several observational studies of PARDS patients, all published since 2007, each including 12-30% sepsis-induced PARDS [264][265][266][267][268][269][270][271][272][273][274][275][276].…”
Section: Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…In ICM in 2017, the Paediatric Mechanical Ventilation Consensus Conference (PEMVECC) developed and voted on 152 recommendations about paediatric mechanical ventilation [12]. However, data from randomised clinical trials were available for only three topic areas and most recommendations were either deferred *Correspondence: WeissS@email.chop.eduor based on low-to-moderate evidence.…”
Section: Mechanical Ventilationmentioning
confidence: 99%